Lyonetiidae of Turkey with notes on their distribution and zoogeography (Lepidoptera) - Seven, Selma (Zootaxa, 2006)
Five species of Lyonetiidae are reported from Turkey: Lyonetia prunifoliella (Hübner, 1796), Lyonetia clerkella (Linnaeus, 1758), Leucoptera malifoliella (Costa, 1836), Bedellia somnulentella (Zeller, 1847), and Leucoptera laburnella (Stainton, 1851). The last was collected from Genista tinctoria in Ordu province and is considered a new pest in Turkey.